Urban nature new directions for city futures - McCormick, Kes; Kiss, Bernadett; Palgan, Yuliya Voytenko; Bulkeley, Harriet 1972-; Davis, McKenna; Raven, Rob 1975-; Luque-Ayala, Andrés (Cambridge University Press, 2025)
"This introductory textbook with a global scope provides training for students of geography, sustainability, and urban and environmental studies in transforming cities to meet climate, biodiversity, and sustainability challenges. The authors tell an inspiring story of how nature can help us re-imagine our cities and their futures"--